Flipping a Coin: Theory and Evidence - Nadja Dwenger; Dorothea Kübler; Georg Weizsäcker (Center for Economic Studies and ifo Institute (CESifo), 2014)
We investigate the possibility that a decision-maker prefers to avoid making a decision and instead delegates it to an external device, e.g., a coin flip. In a series of experiments the participants often choose lotteries between allocations, which contradicts most theories of choice such as expected utility but is consistent with a theory of responsibility aversion that implies a preference for randomness. A large data set on university applications in Germany shows a choice pattern that is also consistent with this theory and entails substantial allocative consequences.
Keywords: D03; D01; 330; preference for randomization; menu-dependent preference; individual decision making; university choice; matching